Predicting Workplace Happiness with PERMA+V Framework in the Context of Banking Sector of Nepal - Thapa, Makshindra (Journal of Development and Administrative Studies, 2025)
The study of workplace happiness is getting more attention since it ensures long-term success of institutions. This study aims to analyze workplace happiness of Nepalese banking sector predicted by six dimensions of PERMA+V framework. The casual comparative research design used and data were collected with structured questionnaire survey. The study samples consist of 278 employees of both managerial and non-managerial positions from banking sectors adopting convenient and snowball techniques. The multiple regression analysis was conducted to assess effect of selected predictors on workplace happiness. The results have shown mixed effects of the predictors. Among six dimensions, two predictors demonstrated significant effects on workplace happiness whereby effects of vitality were strongly positive and considerable positive of positive emotion dimension. Engagement also demonstrated weak positive effect but three other dimensions- relation, meaning and achievement did not predict workplace happiness of the employees. The findings of this study contribute by understanding workplace happiness, a complex construct with adoption of six dimensions used in PERMA+V framework. It provides valuable insights guiding future studies and assisting organization in formulating policies and strategies to retain happy workforce.